2002
DOI: 10.1038/sj.bjc.6600163
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Lsm1 is involved in human prostate cancer progression

Abstract: Elucidation of genetic alterations is an approach to understanding the underlying molecular mechanisms of progression of human prostate cancers. We have searched for genes differentially expressed in advanced prostate cancers using cDNArepresentational difference analysis, and thereby isolated the Lsm1 as one of down-regulated gene. An Lsm1 expression vector was transfected into PC3 cells, normally featuring down-regulated Lsm1, and four transfectants were established. No differences in morphology or cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…They also reported that CaSm was not expressed in two prostate cancer-derived cell lines, PC3 and DU145 (33). In this study, we find that CaSm protein expression is low in primary normal prostate epithelial cells compared with prostate cancer-derived cell lines.…”
Section: Discussionmentioning
confidence: 51%
“…They also reported that CaSm was not expressed in two prostate cancer-derived cell lines, PC3 and DU145 (33). In this study, we find that CaSm protein expression is low in primary normal prostate epithelial cells compared with prostate cancer-derived cell lines.…”
Section: Discussionmentioning
confidence: 51%
“…LSM1 is mapped on chromosome 8p11.2, which has been identified in both prostate cancer [78] and CRC. Although SMN1 has not been identified in cancer directly, it has been proposed to interact with BCL-2, which is associated with CRC, and has a high prognostic value [84,85]. From this analysis, it can be stated that common and unique cliques identified across population networks are involved in important biological processes in CRC.…”
Section: Resultsmentioning
confidence: 99%
“…The first study, using human primary and metastatic prostate samples, concluded that Lsm1/CaSm serves as a metastasis suppressor in prostate cancer samples. 32 The investigators also noted that stable Lsm1 transfection in PC3 cells did not increase proliferation or invasion in vitro . 32 These results are directly at odds with our work and difficult to rationalize given not only the data presented here but also in the context of other investigations supporting that CaSm overexpression promotes a tumorigenic phenotype in many cancer pathologies, including prostate cancer.…”
Section: Discussionmentioning
confidence: 98%